The ins and outs of injection in Western Australia - Carruthers, Susan (Informa Healthcare, 2003)
Hepatitis C is now the most commonly reported infectious disease in Australia and more than 90% of all infections are the result of injecting drug use. Efforts in Australia to reduce the transmission of this virus among injecting populations have largely been unsuccessful, although there is some evidence that incidence and prevalence rates in this country are declining. While the sharing of needles and syringes probably remains the risk of highest magnitude, the sharing of other equipment, the receiving or giving of injections and other practices involved in the injection of drugs are also implicated in the transmission of hepatitis C. This paper reports the findings from an in-depth examination of the act of injection using a recorded observation method. The findings indicate that there are multiple opportunities throughout the process of injection which could contribute to transmission. In particular, the degree of physical contact between those injecting contributes to the risk of contact with possibly infected blood. The implications of these findings on the design of prevention material are discussed.